PENTINGNYA MEMILIH JAJANAN SEHAT DEMI KESEHATAN ANAK - Titik Nurbiyati (Asian Journal of Innovation and Entrepreneurship, 2014)
Availability and food security is a basic of human right. One group of people whooften have problems as a result of food poisoning are school children. Snacks holds animportant role in providing energy intake and other nutrients for children of school age.Snacksat school less assured health can potentially cause poisoning, indigestion and ifprolonged will lead to poor nutritional status. Additionally, unhealthy snacks can cause achild's performance in school were also disrupted. BasedonExtraordinary event, thechild snacks in 2004-2006, a group of elementary school students (SD) most oftensuffered food poisoning school children. Health education plays change the behavior of aperson's health as a result of the learning experience. Therefore, there should bedissemination to provide additional knowledge to parents and children about theimportance of choosing snacks. By knowing the characteristics of unhealthy snacksandthe dangers of unhealthy snacks, parents can teach children the characteristics ofunhealthy snacks so that children do not buy unhealthy snacks or parents can bringsupplies for their children, so that the food goes into the child's body proved hygieneand health.